Epilepsy and preventive antiepileptic treatment in tuberous sclerosis complex. Literature review - I. Kasiulevičiūtė (Neurologijos seminarai)
Tuberous sclerosis complex (TSC) is a rare genetic disorder characterized by the presence of benign tumors in many organs. The pathogenic mutation is found in either the TSC1 or TSC2 tumor suppressor genes. The presence of cortical or subcortical tubers is associated with focal epileptiform discharges on the electroencephalogram and subclinical seizures prior to the onset of clinical seizures. It is known that epileptic seizures in tuberous sclerosis are very resistant to the treatment, therefore, developmental delay usually occurs. In the last decade, more attention has been paid to early recognition and control of seizures (with vigabatrin or everolimus) in tuberous sclerosis complex, as this is highly correlated with improved developmental and neurological outcomes. The article reviews epilepsy and preventive antiepileptic treatment for tuberous sclerosis complex.